Role of cellular NADP+/NADPH ratio in the acclimative mechanism of two common bean cultivars toward salt stress - Ghada Saber Mohamed Ismail; Awatif Saad Ali; Eman Mohammad Mustafa Eldebawy; Nabil El-Sayed Saber (Journal of applied botany and food quality, 2017)
This study is aimed to evaluate the adaptive mechanism in two common bean (Phaseolus vulgaris L.) cultivars, cv. Bronco and cv. Paulista subjected to different concentrations of NaCl (0, 25, 50 and 75 mM). Salt treatments resulted in a significant decrease in the fresh and dry biomasses of shoots and roots as well as leaf relative water content (RWC) in both bean cultivars. Salt stress determines a diversion of plant metabolism towards the synthesis of phenolics, proline and trigonelline (TRG) components together with an increase in the NADP+/NADPH ratio. This increase was accompanied with a significant increase in glucose-6-phosphate dehydrogenase (G-6-PDH) and L-phenylalanine ammonia-lyase (PAL) activities in both bean cultivars. Furthermore, increasing NaCl levels induced oxidative stress measured in terms of malondialdehyde and H2O2 contents. Salt stress triggered an increase in guaiacol peroxidae (GPX) activity in both bean cultivars, whereas polyphenol oxidase (PPO) activity increased only in Bronco plants. The results are discussed in the light of possible roles and regulation of cellular redox potential (NADP+/NADPH) in the maintenance of acclimative mechanism in the two common bean cultivars grown under NaCl stress.